Peningkatan Hasil Belajar IPAS Materi Sistem Pencernaan Manusia melalui Penerapan Game Based Learning pada Siswa Kelas V SDN Dukuh Kupang 3/490 Surabaya - Selviari Selviari; Cholifahtur Rosidah; Rosmiati Rosmiati (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to analyze the effectiveness of implementing Game Based Learning (GBL) in improving students' learning outcomes on the human digestive system material in grade V at SDN Dukuh Kupang 3/490 Surabaya. The research employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design involving two groups: the experimental group (15 students) taught using GBL and the control group (15 students) taught using conventional methods. Data were collected through learning outcome tests (pretest and posttest), observation sheets, and learning motivation questionnaires. Data analysis used the independent sample t-test to examine differences in learning outcomes between the two groups. The results showed that the posttest average score of the experimental group (85.7) was significantly higher than that of the control group (74.3), with p < 0.05. Additionally, observations indicated that active student engagement in the experimental group reached 91%, while the control group only achieved 72%. The application of GBL also increased students' learning motivation, with the motivation score of the experimental group rising from 67.8% to 88.5%. This study concludes that the implementation of Game Based Learning is effective in enhancing learning outcomes, engagement, and motivation in IPAS lessons on the human digestive system material. These findings recommend GBL as an innovative teaching method for improving educational quality in elementary schools.